(untitled) (Experimental biology, 2015)
In the current work analysis of methods of inducing homozygocity in plants as well as the primary protocol of microspore culture for the Australian commercial wheat cv. Gladius are presented. Microspore cultures of the Kazakh cultivars Kazakhstanskaya 19, Kazakhstanskaya rannespelaya, Karabalykskaya 90, Erytrospermum 841, Celinnaya 3С were established based on the new protocol. Microspore divisions could be induced for all tested wheat cultivars. Embryo-like structures were obtained for cvs Kazakhstanskaya 19 and Kazakhstanskaya rannespelaya.